Leg stereotypy syndrome: phenomenological and quantitative analysis - Yilmaz, Abdullah Yasir; Ruzicka, Evzen; Jankovic, Joseph (Journal of neurology, 2024)
BACKGROUND: Leg stereotypy syndrome (LSS) is a very common, yet underrecognized condition. The pathophysiology of the condition is not well understood. OBJECTIVE: To evaluate and describe the visual kinematic characteristics of the repetitive leg movements in individuals with LSS. METHODS: In this study, we identified and videotaped individuals diagnosed with LSS at the Parkinson's Disease Center and Movement Disorders Clinic, Baylor College of Medicine, Houston, Texas between 2000 and 2023. Only patients with LSS and without any co-morbidities were included in the study. Their medical records were carefully reviewed, and the demographic and clinical data were entered into a database. Video recordings of the repetitive leg movements were then analyzed using TremAn software. RESULTS: We identified 14 individuals with LSS who were videotaped at our center. The videos of the 5 cases were too brief and therefore not suitable for TremAn quantitative analysis. The remaining 9 individuals exhibited regular rhythmic oscillations of the legs. Among these, two individuals displayed rhythmic movements only in video segments where their legs were in crossed positions. The other 7 individuals had regular rhythmic oscillations, always with the toes resting on the floor with the heels raised. Frequency analysis showed values between 4.5 and 6.5 Hz, fairly consistent with a variance below 0.5 Hz in individual cases. The oscillation frequency changed from 5.7 Hz to 2.7 Hz while standing. CONCLUSION: In this study, 6 of 9 individuals with LSS showed 4.5-6.5 Hz regular rhythmic leg movements. Studies involving a larger LSS population with additional electrophysiological evaluations are needed to obtain further insights into this common movement disorder.
Keywords: dospělí; bérec; Female; Stereotypic Movement Disorder; Semi-voluntary; Adult; Leg; ženské pohlaví; lidé; Video Recording; biomechanika; Male; Aged; Fidgeting; Leg stereotypy syndrome; Movement disorders; lidé středního věku; porucha se stereotypními pohyby; Stereotypy; senioři; mužské pohlaví; audiovizuální záznam; Middle Aged; Biomechanical Phenomena; Humans